Judo technical-tactical dynamics: analysis of attack system effectiveness in high-level athletes - Kashiwagura, D. B.; Courel-Ibanez, J.; Kashiwagura, F. B.; Agostinho, M. F.; Franchini, E. (International Journal of Performance Analysis in Sport, 2021)
This study aimed to determine which attack systems resulted in higher effectiveness in judo combats. We examined 5847 attacks from 152 high-level international male medallist athletes. Both successful (score) and unsuccessful attacks (no-score) were comprehensively analysed including six variables per action: attacker/defender approach, grip, stance, final displacement and direction of attack. Logistic regression, decision tree analyses and odds ratio (OR) were calculated to determine the probability of success for a given attack system. The main results indicated that i) gripping the dorsal region was decisive for an effective attack, ii) Right-Dorsal & Left-Dorsal grip configuration was the most efficient (P < 0.01, OR = 3.08), followed by Right-Dorsal & Left-Sleeve (P < 0.01, OR = 1.79) and Right-Sleeve & Left-Dorsal (P < 0.01, OR = 1.72), iii) hierarchical technical-tactical analysis identified that scoring rates for particular grips were highly influenced by the direction of attack and stance. Since this is the largest study so far examining attack effectiveness in judo, the information herein presented may have relevant implications for coaches by providing a new and practical organisation of combat dynamics and assisting in setting offensive/defensive plans to improve judo performance.